Դրվագներ Վանի նահանգի հոգեւոր-կրոնական եւ եկեղեցական կյանքից - Ավետիս Հարությունյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В статье говорится об ограблении Ахтамарского католикосата Армянской Апостольской Церкви, об участии духовных и светских представителей Вана в избрании католикоса 30 октября 1908 года и о движении нового поколения в борьбе против армянской церкви. In the article the following problems are presented: the problem of pillage of Aghtamar patriarchal cathedral; problems connected with the participation of spiritual and secular representatives in patriarchal elections of Van on 1908 October 30; problems concerning to the establishment of relations with English Church; problems connected with Saint Geghard’s religious worship which was highly respected among Christians and Muslims in Van.
Keywords: Christianity; History of the Armenian Church